Time-dependent occurrence of false positive amphetamine test strips results after consumption of OTC preparations with pseudoephedrine - Nenić, Ivana; Baralić, Katarina; Javorac, Dragana; Buha Djordjević, Aleksandra; Antonijević Miljaković, Evica; Antonijević, Biljana; Bulat, Zorica; Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
Amphetamine is a potent stimulant of central nervous system and one of the most often abused substances. Immunochromatographic test panels for preliminary urineanalysis are used to track its abuse. Immunochromatographic analysis is quick, simple and based on the principle of competitive binding. Its main disadvantage is cross reactivity - tendency of antibodies to bind structurally similar compounds, including pseudoephedrine. This study aimed to examine the effect of pseudoephedrine-based OTC preparations on the occurrence of false-positive results of preliminary amphetamine urineanalysis and determine the time period during which these results may occur. The study included two subjects. TylolHot® was used for two days, while, on the first day, single dose was administered. On the second day, preparation was administered according to the dosing regimen recommended by the manufacturer (three times a day). Urine samples were collected for three consecutive days. Analysis was performed by immunochromatographic test strips "DIAQUICK" Multi-Drug Test Panels. TylolHot® use led to false positive results for amphetamine 3.75 h after single administration, and lasted for 27 h with repeated administration. After the application of the tested preparation, false positive results on amphetamine were obtained in different time periods, which depended on the intra- and interindividual variations, as well as the dosing regimen. Although test strips are used for quick preliminary analysis, it is necessary to check the results via confirmation methods (gas or liquid chromatography coupled to mass spectrometry). The obtained results are significant during routine testing of patients, employees, students, athletes and members of the army.